Channel prediction in non-regenerative multi-antenna relay selection systems - McLoughlin, Ian Vince (2013)
The use of multiple antennas in two-hop amplify-and-forward relay selection is analysed, where the source, relay and destination are each equipped with multiple receive but single transmit antennas. Since relay switching is based upon feedback information which is delay-limited, channel power prediction is employed to mitigate against the effect of outdated channel state information being used to make switching decisions. During transmission, a source selects a best relay on the basis of predicted signal-to-noise ratio over all available links. A chosen relay then employs maximal ratio combining at its receiver, and applies a variable gain to the received signal before forwarding to the destination. Closed form outage probability and bit error rate solutions are found for arbitrary numbers of relays and receive antennas, and used to explore trade offs between number of relays and number of antennas compared with single antenna alternatives. To assess predictor performance in combatting switching delay, comparison is made to non-predictive systems.